This is arithmetic progression with common difference of minus three...
Formula:
First Term +[ (number of term you want-1)*(common difference which is negative 3)]
Example
For the 3RD term: -5
=1+[(3-1)*(-3)]
=1+[-6]
= -5
For 5TH term: -11
=1+[(5-1)*(-3)]
=1+(-12)
=-11
.: For the 21st term:
=1+[(21-1)*(-3)]
=1+[-60]
= -59
:D
26073.
The given sequence is 11, 31, 51, 72 The nth term of this sequence can be expressed as an = 11 + (n - 1) × 20 Therefore, the nth term is 11 + (n - 1) × 20, where n is the position of the term in the sequence.
94-1-6-11
The 'n'th term is [ 4 - 3n ].
One of the infinitely many possible rules for the nth term of the sequence is t(n) = 4n - 1
26073.
The given sequence is 11, 31, 51, 72 The nth term of this sequence can be expressed as an = 11 + (n - 1) × 20 Therefore, the nth term is 11 + (n - 1) × 20, where n is the position of the term in the sequence.
an = an-1 + d term ar-1 = 11 difference d = -11 ar = ar-1 + d = 11 - 11 = 0 The term 0 follows the term 11.
The nth term of the sequence is 2n + 1.
94-1-6-11
I believe the answer is: 11 + 6(n-1) Since the sequence increases by 6 each term we can find the value of the nth term by multiplying n-1 times 6. Then we add 11 since it is the starting point of the sequence. The formula for an arithmetic sequence: a_{n}=a_{1}+(n-1)d
It works out as -5 for each consecutive term
The 'n'th term is [ 4 - 3n ].
The 'n'th term is [ 4 - 3n ].
The 'n'th term is [ 4 - 3n ].
Oh, what a happy little question! If the 20th term in a sequence is 50, that means we're adding the same amount each time. To find the 21st term, we just need to keep adding that same amount. So, if the 20th term is 50, the 21st term would be 50 plus that special amount. Just keep on adding and you'll find your answer, like painting a beautiful little tree in the sunset.
One of the infinitely many possible rules for the nth term of the sequence is t(n) = 4n - 1